Parameter Effects and Kinetics of Ultrasound Assisted Ionic Liquid Mediated Hydro-distillation and Essential Oil Composition of Flowers of Paeonia suffruticosa Andr. 'Jitsugetsu Nishiki' from Central China. Issue 3 (4th May 2019) - Lei, Gaoming; Song, Chaoying; Shi, Haiyu; Xing, Yihao; Song, Xue; Liang, Guojin
Abstract: Parameter effects and kinetics of ultrasound assisted ionic liquid mediated hydro-distillation (UILHD) were investigated. An ionic liquid 1-ethyl-3-methylimidazolium bromide ([C2 C1 im]Br) was employed both as a substrate under sonication and as an additive during distillation. Paeonia suffruticosa Andr. 'Jitsugetsu Nishiki', a widely cultivated ornamental plant in China, was selected as a case study. The optimal condition of UILHD was [C2 C1 im]Br concentration of 10 %, ultrasonic power of 400 W and pretreatment duration of 20 min. Under such a condition, the extraction equilibrium could be basically reached at 35 min of distillation. The kinetics obeyed pseudo-first-order equation. Calculated values of maximum essential oil yield and first-order rate constant were 1.53 g and 0.117 min -1, respectively. The main essential oil components of flowers of P. suffruticosa Andr. 'Jitsugetsu Nishiki' were 1, 3, 5-trimethoxybenzene (16.6 %), tricosane (8.7 %), nerol (8.6 %), nonadecane (6.4 %) and nonanal (5.5 %). The most abundant chemical class was non-terpene hydrocarbons (44.6 %) followed by non-terpene oxygenated compounds (31.2 %) and oxygenated terpenes (22.2 %). UILHD proved to be a promising technique for efficient isolation of essential oils.